Assessment of factors influencing youth involvement in horticulture agribusiness in Tanzania: a case study of Njombe region - Ng'atigwa, A.A.; Hepelwa, A.; Yami, M.; Manyong, Victor (MDPI, 2020)
Involvement of youth in horticulture agribusiness has become a vital approach to create employment opportunities among the youth in Tanzania. This study aimed at examining the extent of youth participation and factors influencing youth involvement in horticulture agribusiness with a focus on innovations in post-harvest management (PHM). Data were collected from a sample of 576 male and female youth in Njombe region using a multi-stage random sampling technique. Data were analyzed using an ordered logit model and descriptive statistics. Results of the ordered logit analysis showed that primary school education, Form IV and above, management innovation, access to credit, good perception of horticulture for agribusiness and improved packaging materials positively and significantly influence youth involvement in horticulture agribusiness. Gender and land size had a negative and significant influence on youth involvement in horticulture agribusiness, as indicated by higher percentages of male youth (59%) participation in the horticulture agribusiness. Therefore, this study suggests increased investment in capacity development of the youth on PHM innovations and the development of rural infrastructure such as agro-processing and storage facilities by the government and private sector. Increasing the availability of improved packaging materials and provision of youth-friendly credit schemes could encourage youth in horticulture agribusiness.